Cambodian Buddhist Monks and Forest - Prak, Samphose; Leeka, Jaras; Keo, Ratanak (Journal of Graduate MCU KhonKaen Campus, 2023)
This academic paper aims to show how the importance of Buddhist monks engaging in the forest. It focuses on the main three points 1) to awareness of the significance of the environment, 2) to reflect on the Buddha’s life always based under trees and living in the forest for the whole of his life 3) to train the mind to cultivate loving-kindness, starting from oneself until the forest. It found that Khmer philosophy has been implied in Cambodian mindset both cultural perspectives and scientific manner for the sake of preventing the forest through Buddhist concepts, Moreover, this paper will reflect what Buddhist monks have done to prevent any illegal forest cutting down through Buddhist approaches such as to ordain the tree and including Dhamma Talk as well.